The Difficulties of Translating English Phrasal Verbs into Arabic that Encountered Sudanese Secondary Students: A Case Study of 3rd. Level Secondary Students in Zalingei Town - Algazoly, Abdallah Adam Osman (مركز السنبلة للبحوث والدراسات, 2021)
Phrasal verbs are created some problems to students' secondary schools in Zalingei town, the Capital of Central Darfur State, Sudan. Students are unable to form or put the phrasal verbs into sentences to express new concepts. Most of them are unable to translate phrasal verbs from English into Arabic Language, Which affects their performance in reading Arabic Language. Therefore, the study carried out to investigate these problems which encountered them so as to find solution to these difficulties. The descriptive analytical method was used. The population of the study includes students and teachers at secondary schools. The sample of the study comprises twenty students at 3rd level and ten teachers. The researcher designed two tools; a questionnaire for teachers and a test for female twenty students to collect the relevant data of the study. The study came up with these results; More than 70% of the teachers agreed that learners need to know and understand the words before begin to translate. More than 60% of the teachers assured that the meaning of phrasal verb is more difficult to the learners so that they are not able to translate them into Arabic. The study recommended that; The ministry of education should have given the opportunity of continuous training for all English language teachers at secondary schools. Teachers in their schools should have provided Students with various activities which contain most frequent English phrasal verbs in different contexts in order to practice them
الجزء الثاني. نيسان 2021
Keywords: التعليم الثانوي -- تدريس اللغة الإنجليزية -- الترجمة -- أشباه الجمل الفعلية -- مدينة زالنجي -- السودان